2020
DOI: 10.1371/journal.pone.0237508
|View full text |Cite
|
Sign up to set email alerts
|

The FUTUREPAIN study: Validating a questionnaire to predict the probability of having chronic pain 7-10 years into the future

Abstract: Objectives The FUTUREPAIN study develops a short general-purpose questionnaire, based on the biopsychosocial model, to predict the probability of developing or maintaining moderate-tosevere chronic pain 7-10 years into the future. Methods This is a retrospective cohort study. Two-thirds of participants in the National Survey of Midlife Development in the United States were randomly assigned to a training cohort used to train a predictive machine learning model based on the least absolute shrinkage and selectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 72 publications
(81 reference statements)
2
4
0
Order By: Relevance
“…For midlife adults who develop chronic pain, the interference of that pain in daily life is predicted by how strained the person’s family relationships were 10 years prior. This finding builds on prior research finding that negative family relationship quality is associated with future pain status (T. T. Brown & Lee, 2020; Woods et al, 2019).…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…For midlife adults who develop chronic pain, the interference of that pain in daily life is predicted by how strained the person’s family relationships were 10 years prior. This finding builds on prior research finding that negative family relationship quality is associated with future pain status (T. T. Brown & Lee, 2020; Woods et al, 2019).…”
Section: Discussionsupporting
confidence: 70%
“…For midlife adults who develop chronic pain, the interference of that pain in daily life is predicted by how strained the person's family relationships were 10 years prior. This finding builds on prior research finding that negative family relationship quality is associated with future pain status (T. T. Brown & Lee, 2020;Woods et al, 2019). It is possible that the association between family strain and chronic pain interference over 10 years may be linked by psychophysiological distress caused or exacerbated by one's negative family relationships.…”
Section: Discussionsupporting
confidence: 61%
“…Out of the total of 27 studies that were identified for the topic of pain, 14 used a prospective cohort design, 197 198 199 200 201 202 203 204 205 206 207 208 209 210 11 used an observational design, 200 204 205 207 210 211 212 213 214 215 216 6 used a retrospective cohort design, 211 214 215 217 218 219 4 used a randomized control trial, 201 212 220 221 1 used a cross-sectional design, 222 and 1 used mixed methods. 223 Most studies used questionnaire/survey data, but eight used administrative databases, 206 207 208 210 212 220 221 222 seven used mobile devices/sensors, 200 203 204 205 210 216 220 and four used a data warehouse or registry.…”
Section: Resultsmentioning
confidence: 99%
“…Studies explored various outcomes including surgical applications such as determination of postsurgical measures based on residual pain, 197 predicting patellofemoral pain 1 year after intervention, 201 predicting neuropathic pain, 202 predicting chronic pain of 7 to 10 years into the future, 217 predicting complex regional pain syndrome, 207 predicting pain relief for knee osteoarthritis patients, 209 detection of pain, 210 214 216 222 and pain intensity estimation/classification. 205 213 215 220 Other outcomes focused on pain as a predictor of anxiety and depression, coronary heart disease, 199 health status, 218 noncancer pain as predictor of brain aging, 208 and length of stay.…”
Section: Resultsmentioning
confidence: 99%
“…A positive answer to this question would have clinical implications: The ability to predict individual treatment response from expectations and certainties could guide treatment selection and might offer novel targets for boosting existing therapies by cognitive interventions. 11,27,33 While some attempts of predicting future pain states exist, 3,7,28,29,41,44 these are mostly not tied to a specific intervention. Furthermore, to our knowledge, there is no study that has tried to exploit individual expectations for predicting treatment outcomes out-of-sample.…”
Section: Discussionmentioning
confidence: 99%